UNIT 1.26 Characterization of Cannabinoid Receptors. Issue 1 (2nd December 2013) - Cox, Richard F.; Rash, Vincent
Abstract: This unit describes the use of cannabinoid radioligands in competitive binding assays for determining affinity parameters (IC50, K i ) of unlabeled compounds at transfected CB1 and CB2 receptors expressed in cell lines. Curr. Protoc. Pharmacol . 63:1.26.1‐1.26.10. © 2013 by John Wiley & Sons, Inc.